Analysis of Income Disparity Fishermen in Papua Barat Daya Regency - Hasbiah, Hasbiah (Jurnal Economic Resource, 2024)
This study analyses income disparity between fishermen and mangrove crab fishermen in Papua Barat Daya Village, Papua Barat Regency. Quantita-tive methods were used with descriptive analysis and statistical tests, in-cluding the Gini Index and two-sample independent t-test. Data were col-lected from 50 fishermen and 50 mangrove crab fishermen through ques-tionnaires related to their monthly income. The results showed that the av-erage income of fishermen was IDR 6.13 million higher than the average in-come of mangrove crab fishermen of IDR 5.26 million. The Gini Index anal-ysis showed a value of 0.32 for fishermen and 0.45 for mangrove crab fish-ermen, indicating greater income inequality among mangrove crab fishermen. The two-sample independent t-test showed that the difference in in-come between the two groups of fishermen was statistically significant (p < 0.05). This study concludes that there is significant inequality in income between fishermen and mangrove crab fishermen, with higher inequality oc-curring in mangrove crab fishermen. Policy recommendations to reduce this inequality include improving market access, cultivation technology, and government intervention to support the welfare of fishermen in the man-grove crab sector.